2015
DOI: 10.1007/s11357-015-9858-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of white matter lesions on trunk stability during dual-task walking among older adults with mild cognitive impairment

Abstract: The linkage between gait and cognition has been shown in cases of white matter lesion (WML) that affect gait in older adults. Dual-task walking is believed to be cognitively demanding and to alter trunk movement, and gait impairment in people with mild cognitive impairment (MCI) is highlighted under this condition. However, the association between dual-task walking and structural changes in the brain, particularly with WML, in people with MCI is still unclear. The aim of this study was to examine the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
(80 reference statements)
0
15
0
1
Order By: Relevance
“…Circulating IGF-1 levels and blood pressure measurements Although the factors responsible for the deleterious effects of aging on behavior and neuronal function (Baciu et al 2016;Berghuis et al 2015;Campbell et al 2014;Doi et al 2015;Haider et al 2014;Hofmann et al 2014;Kumar and Thakur 2015;Lopez et al 2014;Manich et al 2014;Salminen et al 2014;Samaras et al 2014;Sarubbo et al 2015;Loprinzi 2016;Wallis et al 2016) are not completely understood, there is strong evidence that in elderly humans a decline in circulating IGF-1 levels (Franco et al 2014) plays a critical pathophysiological role. To understand the effects of IGF-1 deficiency on the cerebral microcirculation in the present study, we used a novel mouse model of adult-onset isolated endocrine IGF-1 deficiency, which phenotypically better mimics age-related IGF-1 deficiency observed in humans that most other available rodent models of GH/IGF-1 deficiency (Arum et al 2014a;Hill et al 2015;Rojanathammanee et al 2014;Wiesenborn et al 2014;Arum et al 2014b;Schneider et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Circulating IGF-1 levels and blood pressure measurements Although the factors responsible for the deleterious effects of aging on behavior and neuronal function (Baciu et al 2016;Berghuis et al 2015;Campbell et al 2014;Doi et al 2015;Haider et al 2014;Hofmann et al 2014;Kumar and Thakur 2015;Lopez et al 2014;Manich et al 2014;Salminen et al 2014;Samaras et al 2014;Sarubbo et al 2015;Loprinzi 2016;Wallis et al 2016) are not completely understood, there is strong evidence that in elderly humans a decline in circulating IGF-1 levels (Franco et al 2014) plays a critical pathophysiological role. To understand the effects of IGF-1 deficiency on the cerebral microcirculation in the present study, we used a novel mouse model of adult-onset isolated endocrine IGF-1 deficiency, which phenotypically better mimics age-related IGF-1 deficiency observed in humans that most other available rodent models of GH/IGF-1 deficiency (Arum et al 2014a;Hill et al 2015;Rojanathammanee et al 2014;Wiesenborn et al 2014;Arum et al 2014b;Schneider et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The associations between spatial, temporal, and spatiotemporal gait parameters and reduced cortical thickness have been widespread across cortical regions. Six studies reported that lower total GM volume was associated with poorer performance on multiple gait measures [17,19,3336] (Table 1). Seven studies showed that smaller GM volume in frontal regions was associated with poorer gait [33,34,3741].…”
Section: Grey Matter (Gm)mentioning
confidence: 99%
“…There is instead a scarcity of data regarding the relationship between HR and cognitive measures, even though a number of studies have investigated the alterations of trunk accelerations in cognitively impaired people using a variety of metrics, including some quite similar in principle to HR [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], concluding that gait outcomes related to speed, regularity, predictability, and stability of trunk accelerations may suitably integrate other physical, cognitive, and behavioral measures, to better identify the extent of a cognitive impairment in the elderly. To the best of our knowledge, only Ijmker and Lamoth [ 35 ] attempted to investigate the existence of a possible relationship between HRs and MMSE score.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also attempted to correlate trunk accelerations features, acquired during walking tests, with clinical characteristics of older adults with cognitive impairments. Their main findings can be summarized as follows: in comparison with unaffected individuals, older adults with cognitive impairments exhibit significant reduced value of the root mean square (RMS) and structure variability of the medio-lateral trunk acceleration [33], significant association of trunk stability measures with the white matter lesions [34] and with cognitive performance [35]. In particular, the study of Ijmker and Lamoth [35] showed that the presence of a cognitive impairment is accompanied by a decrease in smoothness of gait along the walking direction (anteroposterior, AP), as indicated by the significantly reduced value of the corresponding HR.…”
Section: Use Of Accelerometers and Imu To Analyze Gait In Elderly Witmentioning
confidence: 99%
See 1 more Smart Citation